Behind Rural Tourism: A Tool and a Panacea - Yudha Aryo Sudibyo; Novita Puspasari; Yanuar E. Restianto (EKO-REGIONAL, 2019)
After the issuance of the village law, villages in Indonesia are required to be economically independent by utilizing their potentials. This study aims to find out main potentials of villages in Banyumas to be developed into village-owned enterprise business units and explore the reasons why villages choose this potential as a village-owned enterprise business unit. This study uses a qualitative approach with data collection methods using focused group discussion and in-depth interviews. The results of this study indicate that of the seven villages participating in the research, six villages chose rural tourism as the main business unit of their village-owned enterprise. Most villages choose rural tourism because they consider that there has been a successful model of rural tourism enterprises in Indonesia and because rural tourism is considered as a solution to various problems.Keywords: Village Law, Rural Tourism, Village-Owned Enterprise, Village Autonomy.